2015
DOI: 10.1007/s00394-015-1020-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro fermentation of nuts results in the formation of butyrate and c9,t11 conjugated linoleic acid as chemopreventive metabolites

Abstract: This is the first study that demonstrates the ability of the human fecal microbiota to convert polyunsaturated fatty acids from walnuts to c9,t11 CLA as a potential chemopreventive metabolite. In addition, the production of butyrate and reduction in potential carcinogens such as secondary BA and lipid peroxidation products might contribute to the protective effects of nuts regarding colon cancer development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 59 publications
5
30
0
Order By: Relevance
“…Butyrate, one of the main end products of dietary fiber fermentation in the colon, has been extensively studied as an agent with such suppressing activity on colon adenoma or carcinoma cells [13][14][15][24][25][26]. The formation of butyrate and other short-chain fatty acids was also identified recently in FS obtained from nuts including macadamia nuts [27]. Butyrate could therefore be mainly responsible for growth inhibitory effects of macadamia FS observed in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…Butyrate, one of the main end products of dietary fiber fermentation in the colon, has been extensively studied as an agent with such suppressing activity on colon adenoma or carcinoma cells [13][14][15][24][25][26]. The formation of butyrate and other short-chain fatty acids was also identified recently in FS obtained from nuts including macadamia nuts [27]. Butyrate could therefore be mainly responsible for growth inhibitory effects of macadamia FS observed in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…| 1467 concentrations. 27 Therefore, butyrate might be mostly responsible for the induction of antioxidant and phase II enzymes by fermented nut samples which contain up to 1.5 mM butyrate while the blank control only contains 0.4 mM butyrate (FS 5%, respectively). 27 Since FS represent complex mixtures, other nut compounds or metabolites might also contribute to the modulation of ROS eliminating enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…The different nut varieties were subjected to an in vitro simulated digestion and fermentation as described previously 29,30 with slight modifications. 27 In brief, 2 g of ground nuts were reconstituted with anaerobic potassium phosphate buffer (0.1 M, pH 7.0) and incubated with α-amylase (17.4 U/sample from a 1000 U/mL stock solution in 20 mM NaH 2 PO 4 ) and NaCl (0.85%) for 5 min and additionally with pepsin (1.11 mg in 0.94 mL 20 mM HCl, pH 2.0) for 2 h at 37°C. Subsequently, nut samples were incubated with an intestinal extract (2.6 mg pancreatin and 5.0 mg oxgall in 5 mL of 11 mM bicarbonate buffer; pH 6.5) in a dialysis membrane (molecular weight cut off: 500-1000 Dalton) under semi-anaerobic conditions (6 h, 37°C).…”
Section: In Vitro Digestion and Fermentation Of Nutsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that CLA has isomer‐specific bioactive properties. The c 9, t 11‐CLA has the anticancer biological activity (Lu et al, ; Schlörmann et al, ), whereas t 10, c 12‐CLA appears to be specifically related to energy expenditure and adipocyte size (Wang, Goodspeed, Turk, Houston, & den Hartigh, ; Yeganeh, Zahradka, & Taylor, ).…”
Section: Introductionmentioning
confidence: 99%